2014
DOI: 10.1039/c4ra07001a
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystals of Zn(Fe)O-based diluted magnetic semi-conductor as potential luminescent and magnetic bimodal bioimaging probes

Abstract: Nanocrystals of Zn(Fe)O-based diluted magnetic semi-conductor (nanoDMS) have been prepared by forced hydrolysis in polyol medium, using zinc and iron salts, and coated with carboxymethylpullulan (CMP). TEM studies revealed that CMP-nanoDMS are spherical, with average diameters on the order of 20 nm. Hydrodynamic diameters of about 75 nm were found in a physiological medium. NanoDMS were superparamagnetic at body temperature, and exhibited high saturation magnetization values (3.25 emu g À1 ). In aqueous suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
6
1
Order By: Relevance
“…Compared with the other preparations, the additional signal between 46° and 53°, which corresponds to an indexation (400) of the cubic phase, made it possible to conclude that the two Zn 0.54 (Fe) 0.46 O and ZnFe 2 O 4 phases were mixed with a molar proportion determined by refinement of 2.57: 1. In previous works using polyol method the NPs sizes were higher than those obtained in our study: Balti et al: 17 nm [ 20 ], Dinesha et al: 19–34 nm [ 21 ], Ciciliati et al: 11–25 nm [ 31 ], Il’ves et al: 10–20 nm [ 13 ] and Arciniegas-Grijalba et al: 20–35 nm [ 32 ]. Moreover, irrespective of the synthesis method, other studies have observed that the size of Zn(Fe)O NPs decreased with the increase of iron concentration and they noted also the formation of a secondary phase-spinel ZnFe 2 O 4 increasing with the concentration of Fe doping and with the annealing temperature [ 13 ].…”
Section: Resultscontrasting
confidence: 74%
See 3 more Smart Citations
“…Compared with the other preparations, the additional signal between 46° and 53°, which corresponds to an indexation (400) of the cubic phase, made it possible to conclude that the two Zn 0.54 (Fe) 0.46 O and ZnFe 2 O 4 phases were mixed with a molar proportion determined by refinement of 2.57: 1. In previous works using polyol method the NPs sizes were higher than those obtained in our study: Balti et al: 17 nm [ 20 ], Dinesha et al: 19–34 nm [ 21 ], Ciciliati et al: 11–25 nm [ 31 ], Il’ves et al: 10–20 nm [ 13 ] and Arciniegas-Grijalba et al: 20–35 nm [ 32 ]. Moreover, irrespective of the synthesis method, other studies have observed that the size of Zn(Fe)O NPs decreased with the increase of iron concentration and they noted also the formation of a secondary phase-spinel ZnFe 2 O 4 increasing with the concentration of Fe doping and with the annealing temperature [ 13 ].…”
Section: Resultscontrasting
confidence: 74%
“…The formation of Zn(Fe)O crystals without modification of the elementary cell, i.e., leading to the same crystal lattice, is obtained either by substitution of some zinc ions by iron ions or by inclusion of iron ions into tetraedric sites of the hexagonal cell [ 20 , 21 ]. For NP-0.50, we tried to propose a stoichiometry for the hexagonal phase by making the hypothesis of substitution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Semiconductor nanocrystals, known as 'quantum dots' (QDs), have high luminescence efficiency, continuous excitation spectrum, high stability against photobleaching, controllable and narrow emission bands compared with the traditional organic fluorescent dyes, due to the quantum confinement effects [13][14][15][16]. Thus, they are ideal fluorescent dyes to replace organic fluorescent dyes and have attracted increasing interest for bioimaging [17], biolabelling [18], biodetection [19] and clinical diagnosis [20]. Compared with the traditional CdSe QDs that have toxicity in certain conditions [21], ZnSe QDs (without heavy metal ions) are potential blue fluorescent biological labels because of their low cytotoxicity [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%